Assessing Effects of Sediment Delivery to Coral Reefs: A Caribbean Watershed Perspective - Rogers, Caroline S.; Ramos-Scharrón, Carlos E. (Frontiers in Marine Science, 2022)
Coral reefs in the western Atlantic and Caribbean are deteriorating primarily from disease outbreaks, increasing seawater temperatures, and stress due to land-based sources of pollutants including sediments associated with land use and dredging. Sediments affect corals in numerous ways including smothering, abrasion, shading, and inhibition of coral recruitment. Sediment delivery resulting in deposition and water quality deterioration can cause degradation at the spatial scale of corals or entire reefs. We still lack rigorous long-term studies of coral cover and community composition before, during and after major sediment stress, and evidence of recovery after watershed management actions. Here we present an overview of the effects of terrestrial sediments on corals and coral reefs, with recent advances in approaches to watershed assessment relevant to the delivery of sediments to these ecosystems. We present case studies of northeastern Caribbean watersheds to illustrate challenges and possible solutions and to draw conclusions about the current state of knowledge of sediment effects on coral reefs. With a better understanding of erosion and the pathways of sediment discharge to nearshore reefs, there is the increased potential for management interventions.